High precision FRET studies reveal reversible transitions in nucleosomes between microseconds and minutes - Alexander Gansen (Nature Portfolio, 2018)
Nucleosomes compact the genome and regulate access to specific DNA sequences. Here the authors employ single-molecule FRET studies to characterize nucleosome dynamics at different salt concentrations and dissect nucleosome disassembly into elementary steps.